2005
DOI: 10.1080/00365510510025773
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term stability of salivary cortisol

Abstract: The measurement of salivary cortisol provides a simple, non-invasive, and stress-free measure frequently used in studies of the hypothalamic-pituitary-adrenal axis activity. In research projects, samples are often required to be stored for longer periods of time either because of the protocol of the project or because of lack of funding for analysis. The aim of the present study was to explore the effects of long-term storage of samples on the amounts of measurable cortisol. Ten pools of saliva were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
151
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(158 citation statements)
references
References 10 publications
4
151
0
3
Order By: Relevance
“…Neither testosterone nor cortisol was correlated with the time interval between sampling and freezing (p's > .25). In line with this, previous studies have shown that saliva samples can be mailed and/or stored at room temperature for at least 7 days and sometimes up to 4 weeks without cortisol or testosterone levels being affected (Clements & Parker, 1998;Dabbs, 1991;Garde & Hansen, 2005;Gröschl, Wagner, Rauh, & Dörr, 2001;Jensen et al, 2011;Kirschbaum & Hellhammer, 1989.…”
Section: Methodssupporting
confidence: 54%
See 1 more Smart Citation
“…Neither testosterone nor cortisol was correlated with the time interval between sampling and freezing (p's > .25). In line with this, previous studies have shown that saliva samples can be mailed and/or stored at room temperature for at least 7 days and sometimes up to 4 weeks without cortisol or testosterone levels being affected (Clements & Parker, 1998;Dabbs, 1991;Garde & Hansen, 2005;Gröschl, Wagner, Rauh, & Dörr, 2001;Jensen et al, 2011;Kirschbaum & Hellhammer, 1989.…”
Section: Methodssupporting
confidence: 54%
“…On two subsequent workdays, they collected one saliva sample at home after awakening. Self-sampling of saliva has been described as an adequate method for field studies (Garde & Hansen, 2005;Jensen, Hansen, Abrahamsson, & Nørgaard, 2011). It is widely used since it allows participants to collect samples non-invasively in their natural environment directly after awakening (see e.g., Chida & Steptoe, 2009;Gettler, McDade, & Kuzawa, 2011;Perini, Ditzen, Fischbacher, & Ehlert, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…However, an advantage of LNSC measurement is the fact that it is a simple and non-invasive method in the evaluation of patients with suspected hypercortisolism, and it is therefore increasingly used as first-line screening test. Salivary samples can be obtained in ambulatory patients and can be stored at room temperature for several days (35,36,37). A potential concern when saliva sampling is performed at home is contamination with topical or inhaled steroids or collection of insufficient volumes of saliva.…”
Section: Discussionmentioning
confidence: 99%
“…Steroid hormones such as C have generally been considered to be stable in saliva even when stored at room temperature for a number of days [23,56]. However, more recent studies have raised concern with respect to sample treatment and storage prior to analysis [61,117,142].…”
Section: Storagementioning
confidence: 99%
“…However, more recent studies have raised concern with respect to sample treatment and storage prior to analysis [61,117,142]. Concentrations of sal-C were found to decrease by 9.2 % per month in samples stored at room temperature [56] compared to baseline. Toone et al [142] observed that following 7 days of storage at 4 °C, sal-T decreased by 26 ± 15 % whereas sal-C remained unchained compared to baseline.…”
Section: Storagementioning
confidence: 99%